Thermal conductivity of sandwich compounds used in the construction industry - Mendoza, Marco Antonio (2021)
In recent decades sandwich composites have taken a greater share in the construction industry, due to their low cost and properties that characterize these composites. Among the most important properties of these, the thermal conductivity stands out, which is directly linked to the individual's thermal comfort in a building. Currently, the Peruvian State has been developing projects in the fight against frost and cold, where one of the main interventions focuses on the construction of sustainable homes that can help the high Andean population cope with the inclement cold. In this sense, it is necessary to have construction materials appropriate for the climatic conditions of the place, and that is where lies the importance of this research. This paper proposes the study of thermal conductivity at temperature conditions close to 0 ºC of sandwich composites formed from monolithic materials most used in construction such as drywall, brick, expanded polystyrene, glass wool and polyester wool. The study was carried out through the use of a guarded hot plate equipment of double sample, built with the guidelines established by the ASTM C177 standard. The measurements made of the composites drywall-expanded polystyrene-drywall, drywall-glass wool-drywall, drywall-polyester wool-drywall, brick-expanded polystyrene-brick, brick-glass wool-brick, brick-polyester wool-brick, gave the following results 0.0953 Wm-1.ºC-1, 0.0675 Wm-1.ºC-1, 0.0833 Wm-1.ºC-1, 0.0891 Wm-1.ºC-1, 0.0602 Wm-1.ºC-1, 0.0709 Wm-1.ºC-1 respectively.